2019
DOI: 10.1088/1361-6455/ab2362
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous decay rate and Casimir–Polder interaction of a two-level atom in a Bragg-reflector cylindrical structure

Abstract: Spontaneous decay rate and Casimir–Polder interaction of an excited two-level atom enclosed in a distributed-Bragg-reflector cylindrical waveguide are studied. Conditions for resonances to exist are established by comparing the distributed-Bragg-reflector-waveguide results with those of a perfectly reflecting hollow waveguide, and taking advantage of the simplicity of the Green tensor of the latter. The Casimir–Polder potential is obtained and found to exhibit a potential well along the cylinder axis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…where J n (ξ) stands for the first-type Bessel function, For a cylindrical system with a perfectly reflecting wall, standard-mode expansion applies and the h integrals in the Green's tensor can be carried out in closed form [35]. The Green's tensor will then contain an infinite sum over the roots of the Bessel functions.…”
Section: Basic Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…where J n (ξ) stands for the first-type Bessel function, For a cylindrical system with a perfectly reflecting wall, standard-mode expansion applies and the h integrals in the Green's tensor can be carried out in closed form [35]. The Green's tensor will then contain an infinite sum over the roots of the Bessel functions.…”
Section: Basic Formulasmentioning
confidence: 99%
“…They showed that there exists a substantial radiative exchange between distant atoms mediated by guided modes of the nanofiber. Spontaneous decay and van der Waals interaction of an excited atom located on the axis of a cylindrical structure has been discussed in [35]. Dispersion interaction between two atoms being off axis has been discussed in [36].…”
Section: Introductionmentioning
confidence: 99%